Computed Tomography and Magnetic Resonance Imaging of the Coronary Sinus: Anatomic Variants and Congenital Anomalies - Chen, Yingming Amy (Springer Berlin Heidelberg, 2014)
The coronary sinus (CS) is an important vascular structure that allows for access into the coronary veins in multiple interventional cardiology procedures, including catheter ablation of arrhythmias, pacemaker implantation and retrograde cardioplegia. The success of these procedures is facilitated by the knowledge of the CS anatomy, in particular the recognition of its variants and anomalies. This pictorial essay reviews the spectrum of CS anomalies, with particular attention to the distinction between clinically benign variants and life-threatening defects. Emphasis will be placed on the important role of cardiac CT and cardiovascular magnetic resonance in providing detailed anatomic and functional information of the CS and its relationship to surrounding cardiac structures. Teaching Points • Cardiac CT and cardiovascular magnetic resonance offer 3D high-resolution mapping of the coronary sinus in pre-surgical planning. • Congenital coronary sinus enlargement occurs in the presence or absence of a left-to-right shunt. • Lack of recognition of coronary sinus anomalies can lead to adverse outcomes in cardiac procedures. • In coronary sinus ostial atresia, coronary venous drainage to the atria occurs via Thebesian or septal veins. • Coronary sinus diverticulum is a congenital outpouching of the coronary sinus and may predispose to cardiac arrhythmias.